Surgical outcomes of hysterectomy by transvaginal natural orifice transluminal endoscopic surgery (vNOTES) compared with laparoscopic total hysterectomy (LTH) in women with non-prolapsed and benign uterine diseases - Chih-Yi Yang; Te-Chun Shen; Cheng-Li Lin; Yin-Yi Chang; Chen-Chu Huang; Wu-Chou Lin (Elsevier, 2020)
Objective: We aimed to compare the surgical outcomes between hysterectomy by transvaginal natural orifice transluminal endoscopic surgery (vNOTES) and laparoscopic total hysterectomy (LTH). Materials and methods: This study is a retrospective chart analysis. From January 1, 2015, to December 31, 2017, a total of 183 patients of reproductive age with an indication for hysterectomy due to non-prolapsed and benign uterine diseases were enrolled. After exclusion, 20 patients were included in the vNOTES group, and 66 patients were included in the LTH group. Various post-operative surgical outcomes such as operative time, blood loss, uterus weight, a decrease in hemoglobin level on post-operative day one, post-operative pain scale, complications, length of hospitalization, and re-admission rate were measured. Results: No difference was observed between both groups regarding operative time, blood loss, uterine weight, a decrease in hemoglobin level on post-operative day one, complications, hospital stay, and re-admission rate. Patients in the vNOTES group had significantly less post-operative pain compared with those in the LTH group (p = 0.03). Conclusions: The surgical outcomes of hysterectomy by vNOTES could be similar to those of LTH. Patients undergoing hysterectomy by vNOTES may have less post-operative pain compared with those undergoing LTH. However, the sample size was small, and the results need more evidence to confirm these findings.